Game Edukasi Hafalan Surat Pendek Al-Qur’an The Adventure Of Ali - Vadlya Maarif; Hidayat M. Nur; Fitrian Chandrayoga (Universitas Bina Sarana Informatika, 2020)
Abstract: Games at this time become a very popular thing, even early childhood have played games using an Android smartphone. But children tend to play games excessively, that causing concerns for parent about the negative effects of games that affect their children. Therefore the game